2023
DOI: 10.1111/jipb.13484
|View full text |Cite
|
Sign up to set email alerts
|

Auxin signaling module OsSK41‐OsIAA10‐OsARF regulates grain yield traits in rice

Abstract: Auxin is an important phytohormone in plants, and auxin signaling pathways in rice play key roles in regulating its growth, development, and productivity. To investigate how rice grain yield traits are regulated by auxin signaling pathways and to facilitate their application in rice improvement, we validated the functional relationships among regulatory genes such as OsIAA10, OsSK41, and OsARF21 that are involved in one of the auxin (OsIAA10) signaling pathways. We assessed the phenotypic effects of these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The auxin signal transduction pathway, encompassing TIR1/AFB co-receptors, Aux/IAA repressors, and ARF transcription factors, is recognized for its regulatory role in grain yield. In rice, the module of OsSK41-OsIAA10-OsARF is known to regulate grain yield [78]; meanwhile, research has shown that the functions of OsTIR1/AFB genes are redundant for yield in rice [79]. Nevertheless, the module's involvement in the grain filling process remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…The auxin signal transduction pathway, encompassing TIR1/AFB co-receptors, Aux/IAA repressors, and ARF transcription factors, is recognized for its regulatory role in grain yield. In rice, the module of OsSK41-OsIAA10-OsARF is known to regulate grain yield [78]; meanwhile, research has shown that the functions of OsTIR1/AFB genes are redundant for yield in rice [79]. Nevertheless, the module's involvement in the grain filling process remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…The auxin signal transduction pathway, encompassing TIR1/AFB co-receptors, Aux/IAA repressors, and ARF transcription factors, is recognized for its regulatory role in grain yield. Nevertheless, its involvement in the grain filling process remains ambiguous [78,79]. SAUR genes, which are early auxin-responsive genes, play a role in plant growth, particularly in cell elongation [80].…”
Section: Discussionmentioning
confidence: 99%